Art therapy as a comprehensive complementary treatment for Parkinson’s disease - Ettinger, Tom; Berberian, Marygrace; Acosta, Ikuko; Cucca, Alberto; Feigin, Andrew; Genovese, Danilo; Pollen, Travis; Rieders, Julianne; Kilachand, Rohita; Gomez, Clara; Kaimal, Girija; Biagioni, Milton; et al. (Frontiers in Human Neuroscience, 2023)
Introduction Parkinson’s disease (PD) is the second most prevalent neurodegenerative disease. Complementary and alternative therapies are increasingly utilized to address its complex multisystem symptomatology. Art therapy involves motoric action and visuospatial processing while promoting broad biopsychosocial wellness. The process involves hedonic absorption, which provides an escape from otherwise persistent and cumulative PD symptoms, refreshing internal resources. It involves the expression in nonverbal form of multilayered psychological and somatic phenomena; once these are externalized in a symbolic arts medium, they can be explored, understood, integrated, and reorganized through verbal dialogue, effecting relief and positive change. Methods 42 participants with mild to moderate PD were treated with 20 sessions of group art therapy. They were assessed before and after therapy with a novel arts-based instrument developed to match the treatment modality for maximum sensitivity. The House-Tree-Person PD Scale (HTP-PDS) assesses motoric and visuospatial processing–core PD symptoms–as well as cognition (thought and logic), affect/mood, motivation, self (including body-image, self-image, and self- efficacy), interpersonal functioning, creativity, and overall level of functioning. It was hypothesized that art therapy will ameliorate core PD symptoms and that this will correlate with improvements in all other variables. Results HTP-PDS scores across all symptoms and variables improved significantly, though causality among variables was indeterminate. Discussion Art therapy is a clinically efficacious complementary treatment for PD. Further research is warranted to disentangle causal pathways among the aforementioned variables, and additionally, to isolate and examine the multiple, discrete healing mechanisms believed to operate simultaneously in art therapy.